Analisis Implementasi Peraturan Daerah Nomor 16 Tahun 2014 Tentang Kawasan Tanpa Rokok Berdasarkan Akreditasi Di SMP Negeri 2 - Suaib, Suaib (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The smoking problem has always been the center of attention, not only nationally, but even internationally. The impacts that occur involve various aspects, especially health aspects which are clearly very easily exposed to cigarettes. The aim of the research is to find out how to implement Banggai Regency Regional Regulation Number 16 of 2014 concerning Non-Smoking Areas Based on Accreditation at SMP Negeri 2 Kintom, Banggai Regency. This research method is qualitative research with a descriptive approach to explore phenomena and information regarding the implementation of Banggai Regency Regional Regulation Number 16 of 2014 concerning Non-Smoking Areas Based on Accreditation at SMP Negeri 2 Kintom Banggai Regency using in-depth interviews and continuous observation during The research took place in a Junior High School (SMP) environment. Based on the results of the FGD from several students at SMPN 2 Kintom, in general what they know is that there is no specific committee or working group for implementing KTR.